Iron in a Cage: Fixation of a Fe(II)tpy2 Complex by Fourfold Interlinking. Issue 37 (29th June 2020) - Brandl, Thomas; Johannsen, Sven; Häussinger, Daniel; Suryadevara, Nithin; Prescimone, Alessandro; Bernhard, Stefan; Gruber, Manuel; Ruben, Mario; Berndt, Richard; Mayor, Marcel
Abstract: The coordination sphere of the Fe(II) terpyridine complex 1 is rigidified by fourfold interlinking of both terpyridine ligands. Profiting from an octa‐aldehyde precursor complex, the ideal dimensions of the interlinking structures are determined by reversible Schiff‐base formation, before irreversible Wittig olefination provided the rigidified complex. Reversed‐phase HPLC enables the isolation of the all‐ trans isomer of the Fe(II) terpyridine complex 1, which is fully characterized. While temperature independent low‐spin states were recorded with superconducting quantum interference device (SQUID) measurements for both, the open precursor 8 and the interlinked complex 1, evidence of the increased rigidity of the ligand sphere in 1 was provided by proton T2 relaxation NMR experiments. The ligand sphere fixation in the macrocyclized complex 1 even reaches a level resisting substantial deformation upon deposition on an Au(111) surface, as demonstrated by its pristine form in a low temperature ultra‐high vacuum scanning tunneling microscope experiment. Abstract : Caging an Fe(II) ion : Like a cube the fourfold interlinked bisterpyridine ligand surrounds the Fe(II) ion. The post‐coordinative macrocyclization rigidifies the ligand sphere and guaranties the preservation of the properties of the complex.